Optimization of fluorescence and surface adsorption of citric acid/ethanolamine carbon nanoparticles for subsurface tracers. (November 2020) - Sinclair, Laura; Brown, Joseph; Salim, Muhammad G.; May, Daniel; Guilvaiee, Bahareh; Hawkins, Adam; Cathles, Lawrence
Abstract: The tunable fluorescence and biocompatibility of fluorescent carbon nanoparticles (FCNs) makes them appealing tracers in geothermal, environmental, and clinical applications. Here, we address FCNs synthesized from reaction and pyrolysis of citric acid and ethanolamine. We examine the fluorescence and the adsorption of these FCNs as critical parameters that influence their use in applications. FCN fluorescence was observed to develop during pyrolysis and measured at pyrolysis temperatures ranging from 190 to 250 °C. Transmission electron microscopy shows that the FCN average diameter of approximately 13 nm is unaffected by pyrolysis temperature. However, pyrolysis temperature strongly affects fluorescence, which peaks at 210 °C. The surface hydrophobicity of the FCNs increases with pyrolysis temperature as measured by retention on reverse phase chromatography. Together, these results suggest that particle surface functionalities provide both fluorescence and hydrophilicity, and that these surface functionalities are destroyed with excessive pyrolysis. To examine their surface adsorption, quartz crystal microbalance measurements demonstrate that pyrolysis temperature increases FCN adsorption on mineral surfaces. Surfaces with greater hydrophobicity show greater FCN adsorption. Adsorption is unaffected by the presence of mono- or divalent ions in solution. This suggests adsorption by hydrophobic interaction for the Fe2 O3, SiO2, and AlSiO surfaces studied. Graphical abstract: Image 1